Positive electrode material and preparation method thereof, positive electrode plate, battery and electric device

By using lithium iron phosphate as the core and carbon cladding in the positive electrode material of lithium battery, combined with ball milling, sand milling and sintering processes, the problem of insufficient circulation performance of lithium batteries is solved, and lower water absorption and higher circulation performance are achieved.

CN119833583APending Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202410043846.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-11
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The circulation performance of existing lithium batteries is insufficient, mainly due to the water absorption of the positive electrode material, causing side reactions between water and electrolyte, which damages the negative electrode SEI film.

Method used

A positive electrode material containing lithium iron phosphate or M-containing lithium iron phosphate as the core and the coating layer contains carbon or carbon and M-containing elements. Through ball milling, sand milling and sintering processes, the powder resistivity and BET specific surface area are controlled to reduce the water absorption of the positive electrode material.

Benefits of technology

It effectively reduces the water absorption rate and water absorption contact area of ​​the positive electrode material, reduces the side reaction between water and electrolyte, and significantly improves the circulation performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833583A_ABST
    Figure CN119833583A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a preparation method of the positive electrode material, a positive electrode plate, a battery and an electric device. The positive electrode material comprises an inner core and a coating layer coating the inner core, the inner core comprises lithium iron phosphate or lithium iron phosphate containing an M element, and the coating layer comprises carbon and an optional M element; the positive electrode material satisfies the following conditions: the powder resistivity at 8MPa is less than or equal to 20 omega.cm; and, the BET specific surface area at the liquid nitrogen temperature is 6-15.2 m2 / g. The positive electrode material has few side reactions, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a positive electrode material, a method for preparing the positive electrode material, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As secondary batteries have made great progress, higher requirements have been put forward for their cycle performance. Summary of the invention

[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode material, a method for preparing the positive electrode material, a positive electrode sheet, a battery and an electrical device. The positive electrode material of the present application has fewer side reactions and less loss of active lithium, thereby improving the cycle performance of the battery.

[0004] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode material, comprising a core and a coating layer coating the core, wherein the core comprises lithium iron phosphate or lithium iron phosphate containing an M element, and the coating layer comprises carbon or comprises carbon and an M element; wherein the M element in the core and the coating layer independently comprises one or more elements of Group IIA, Group IIIA, Group IVA, Group IVB, and Group VB, and may be selected to comprise one or more elements of Si, Al, B, Mg, Zr, Ti, Nb, and V;

[0005] Furthermore, the positive electrode material satisfies:

[0006] Powder resistivity at 8 MPa ≤ 20 Ω·cm; and,

[0007] The BET specific surface area at liquid nitrogen temperature is 6-15.2 m 2 / g.

[0008] The positive electrode material of the present application has both a low water absorption rate and a low water absorption contact area, which reduces the water absorption of the positive electrode material and reduces the occurrence of side reactions between water in the positive electrode material and the electrolyte, thereby improving the cycle performance of the battery.

[0009] In any embodiment, the powder resistivity of the positive electrode material at 8 MPa is ≤10Ω·cm; and / or,

[0010] The BET specific surface area of ​​the positive electrode material at liquid nitrogen temperature is 8-11 m 2 / g.

[0011] In any embodiment, the amount of iron dissolved per gram of the positive electrode material in 100 mL of hydrochloric acid solution is ≤ 60 ppm; and / or,

[0012] The primary particle size distribution consistency index (PDI) of the positive electrode material is ≤0.87.

[0013] In any embodiment, the amount of iron dissolved per gram of the positive electrode material in 100 mL of hydrochloric acid solution is ≤55 ppm; and / or,

[0014] The primary particle size distribution consistency index (PDI) of the positive electrode material is ≤0.4.

[0015] The iron dissolution amount of the positive electrode material of the present application meets the above range, which can improve the situation where iron settles at the negative electrode and destroys the formation of SEI film, thereby improving the cycle performance of the battery.

[0016] The consistency index PDI of the primary particle size distribution of the positive electrode material of the present application satisfies the above range, which is beneficial to controlling the concentration and uniformity of the primary particle size of the positive electrode material, reducing the precipitation of small particle metal ions and / or reducing the occurrence of side reactions with the electrolyte after large particles are crushed, thereby improving the cycle performance of the battery.

[0017] In any embodiment, the weight content of the carbon in the positive electrode material is 1.2%-2.0%; and / or,

[0018] The weight content of the M element in the positive electrode material is 297ppm-10 4 ppm.

[0019] In any embodiment, the weight content of the M element in the positive electrode material is 10 3 ppm-10 4 ppm.

[0020] This is conducive to obtaining a coating layer with thin thickness, good integrity, high density, high uniformity, and high degree of graphitization, thereby improving the cycle performance of the battery.

[0021] In any embodiment, the Dv50 particle size of the positive electrode material is 0.6-1.5 μm; and / or,

[0022] The compaction density of the positive electrode material at 221.55 MPa is ≥ 2.3 g / cm 3 .

[0023] This is conducive to obtaining a positive electrode sheet with high compactness and high compaction density.

[0024] The second aspect of the present application also provides a method for preparing a positive electrode material, comprising:

[0025] Ball-milling and sand-milling an iron source, a lithium source, a phosphorus source, an organic carbon source and an inorganic carbon source in a solvent to obtain a mixture;

[0026] Drying and sintering the mixture to obtain a positive electrode material;

[0027] The positive electrode material is the positive electrode material of the first aspect of the present application.

[0028] Therefore, the present application adopts the above-mentioned raw materials and combines them with operations such as ball milling, sand milling, and sintering, and optionally adds doping elements in the coating layer, so that the powder resistivity and BET specific surface area of ​​the positive electrode material meet the above-mentioned ranges, so that the prepared positive electrode material has both a lower water absorption rate and a lower water absorption contact area, thereby reducing the water absorption of the positive electrode material and reducing the occurrence of side reactions between water in the positive electrode material and the electrolyte, thereby improving the cycle performance of the battery.

[0029] In any embodiment, the organic carbon source includes a small molecule organic carbon source and a medium molecule organic carbon source, or includes a small molecule organic carbon source and a high molecule organic carbon source.

[0030] In any embodiment, the weight ratio of the small molecule organic carbon source to the medium molecule organic carbon source, or the weight ratio of the small molecule organic carbon source to the high molecule organic carbon source is 1:9-9:1; and / or,

[0031] The weight average molecular weight of the medium molecular organic carbon source is greater than 500 and less than or equal to 2000; and / or,

[0032] The weight average molecular weight of the polymer organic carbon source is greater than 2000 and less than or equal to 1000000; and / or,

[0033] The inorganic carbon source includes one or more of acetylene black, Ketjen black, graphite oxide, graphene, and carbon nanotubes.

[0034] This is conducive to forming a coating layer with good density and integrity, thereby reducing the iron dissolution and powder resistivity of the positive electrode material. Inorganic carbon sources act as a supporting skeleton during the carbonization process of organic carbon sources, which can improve the uniformity and integrity of carbon film formation.

[0035] In any embodiment, the organic carbon source includes one or more of glucose, sucrose, fructose, citric acid, starch, polyvinyl alcohol, polyethylene glycol, and polyaniline.

[0036] In any embodiment, in the step of preparing the mixture, the iron source, lithium source, phosphorus source, organic carbon source, inorganic carbon source, and source of element M are ball-milled or sand-milled in a solvent to obtain a mixture.

[0037] In any embodiment, the weight ratio of the inorganic carbon source to the iron element in the iron source is 1:50-1:345.

[0038] In any embodiment, the Dv50 particle size of the insoluble particles in the mixture is 0.40-0.85 μm; and / or,

[0039] The sanding temperature is 25°C-35°C; and / or,

[0040] The sanding time is 0.5-4 hours; and / or,

[0041] Sand at 5000-10000 rpm.

[0042] This is beneficial to improving the consistency of the primary particle size distribution of the positive electrode material, improving the concentration and uniformity of the positive electrode material particles, reducing the precipitation of small particle metal ions and / or the side reaction of large particles with the electrolyte after crushing, and improving the cycle performance of the battery.

[0043] In any embodiment, the method further comprises: before sintering, granulating the dried mixture to obtain particles; wherein the average particle size of the particles is 2 mm-10 mm; and / or,

[0044] The method further comprises: after sintering, crushing the sintered product to obtain the positive electrode material, thereby facilitating improving the consistency of the primary particle size distribution of the positive electrode material.

[0045] In any embodiment, after drying or granulation, the temperature is uniformly raised to the sintering temperature within 2.5-9 hours; and / or,

[0046] The sintering temperature is 600° C.-800° C.; and / or,

[0047] The sintering time is 5-10 hours; and / or,

[0048] Heating and sintering in a reducing atmosphere; and / or,

[0049] The volume content of the reducing gas in the reducing atmosphere is 2%-8%.

[0050] Therefore, on the one hand, it is beneficial to fully crack and carbonize the organic carbon source to obtain an ultra-thin coating layer with a high degree of graphitization; on the other hand, it is beneficial to improve the uniformity of the coating layer and reduce the problem of metal ion dissolution caused by uneven or incomplete coating.

[0051] In any embodiment, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is 0.96-0.98; and / or,

[0052] The molar ratio of the lithium element in the lithium source to the iron element in the iron source is 1.015-1.045; and / or,

[0053] The molar ratio of the M element to the iron element in the iron source is 1:1000-3:100; and / or,

[0054] The Dv50 particle size of the insoluble particles in the ball-milled material is 2.0-5.0 μm.

[0055] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the method of the second aspect of the present application.

[0056] The fourth aspect of the present application provides a battery, comprising the positive electrode material of the first aspect of the present application, the positive electrode material prepared by the method of the second aspect of the present application, or the positive electrode plate of the third aspect of the present application.

[0057] The fifth aspect of the present application provides an electrical device, comprising the battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0059] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0060] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0061] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0062] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0063] Figure 6 It is a schematic diagram of an electrical device using a battery cell according to an embodiment of the present application as a power source.

[0064] Figure 7 This is a SEM photograph of the positive electrode material of Example 1 of the present application.

[0065] Description of reference numerals:

[0066] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0067] Hereinafter, the embodiments of the positive electrode material and preparation method thereof, positive electrode sheet, negative electrode sheet, battery cell, battery module, battery pack and electric device of the present application are specifically disclosed with appropriate reference to the drawings in detail. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0068] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0069] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0070] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0071] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0072] If there is no special explanation, the Dv50 particle size in the present application refers to the particle size when the cumulative value of volume distribution is 50%.

[0073] [Battery Cell]

[0074] A battery cell, also known as a rechargeable battery or storage battery, refers to a battery that can be recharged to activate the active material after being discharged and continue to be used.

[0075] Normally, a battery cell includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.

[0076] [Cathode material]

[0077] One embodiment of the present application provides a positive electrode material, comprising a core and a coating layer coating the core, wherein the core comprises lithium iron phosphate or lithium iron phosphate containing an M element, and the coating layer comprises carbon or comprises carbon and an M element; wherein the M element in the core and the coating layer independently comprises one or more elements of Group IIA, Group IIIA, Group IVA, Group IVB, and Group VB, and may be selected to comprise one or more elements of Si, Al, B, Mg, Zr, Ti, Nb, and V;

[0078] Furthermore, the positive electrode material satisfies:

[0079] The powder resistivity at 8 MPa is ≤20Ω·cm, which may be ≤19Ω·cm or ≤18Ω·cm, for example, 0.01Ω·cm, 0.05Ω·cm, 0.1Ω·cm, 0.5Ω·cm, 1Ω·cm, 2Ω·cm, 4Ω·cm, 5Ω·cm, 7Ω·cm, 8Ω·cm, 9Ω·cm, 10Ω·cm, 12Ω·cm, 14Ω·cm, 15Ω·cm, 16Ω·cm, 18Ω·cm, 20Ω·cm or a range formed by using any of the above values ​​as upper limits, or a range consisting of any of the above values; and,

[0080] The BET specific surface area at liquid nitrogen temperature is 6-15.2 m 2 / g, for example 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 15.2m 2 / g or any range consisting of the above values.

[0081] The inventors of the present application have discovered through research that the main mechanisms of battery cycle performance degradation using iron-based polyanion phosphate positive electrode materials include: after the positive electrode material surface absorbs water, water reacts with the electrolyte to generate hydrofluoric acid, and the hydrogen ions destroy the SEI film on the negative electrode surface, or react with the lithium on the negative electrode surface, causing cycle performance degradation.

[0082] Although the mechanism is not clear, the applicant unexpectedly found that:

[0083] The positive electrode material of the present application whose powder resistivity satisfies the above range has a dense and highly graphitized coating layer, which is beneficial to reducing the water absorption rate of the positive electrode material; the BET specific surface area of ​​the positive electrode material of the present application is within the above range, which is beneficial to reducing the water absorption contact area of ​​the positive electrode material; therefore, the positive electrode material of the present application has both a lower water absorption rate and a lower water absorption contact area, which reduces the water absorption of the positive electrode material and reduces the occurrence of side reactions between water and the electrolyte in the positive electrode material, thereby improving the cycle performance of the battery.

[0084] In some embodiments, the core includes Li 1+e M f Fe aPO4, wherein 0≤e<0.1 (e.g., 0, 0.001, 0.003, 0.005, 0.007, 0.008, 0.009, 0.01, 0.02, 0.04, 0.05, 0.07, 0.08, 0.09, 0.095 or any range thereof), 0≤f≤0.05 (e.g., 0, 0.001, 0.003, 0.005, 0.007, 0.008, 0.009 , 0.01, 0.02, 0.04, 0.05 or any range consisting of the above values), 0.95≤a≤1 (for example, 0.95, 0.96, 0.97, 0.98, 0.99, 1 or any range consisting of the above values); the M element includes one or more elements of Group IIA, Group IIIA, Group IVA, Group IVB, and Group VB, and can be selected to include one or more elements of Si, Al, B, Mg, Zr, Ti, Nb, and V.

[0085] In some embodiments, the powder resistivity of the cathode material at 8 MPa is ≤10Ω·cm; and,

[0086] The BET specific surface area of ​​the positive electrode material at liquid nitrogen temperature is 8-11 m 2 / g.

[0087] In some embodiments, the amount of iron dissolved in 100 mL of hydrochloric acid solution per gram of the positive electrode material is ≤60 ppm, optionally ≤55 ppm, and more optionally ≤15 ppm, for example, 5 ppm, 10 ppm, 15 ppm, 17 ppm, 20 ppm, 22 ppm, 25 ppm, 27 ppm, 30 ppm, 33 ppm, 36 ppm, 39 ppm, 40 ppm, 42 ppm, 45 ppm, 47 ppm, 50 ppm, 53 ppm, 55 ppm, 57 ppm, 58 ppm, 59 ppm, 60 ppm, or any of the above values ​​as the upper limit of the range formed, or the range composed of any of the above values; and / or,

[0088] The consistency index PDI value of the primary particle size distribution of the positive electrode material is ≤0.87, which can be selected as ≤0.4, for example, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.6, 0.7, 0.75, 0.8, 0.85, 0.87 or any of the above values ​​as the range consisting of the upper limit of the value, or the range consisting of any of the above values.

[0089] The iron dissolution amount of the positive electrode material of the present application meets the above range, which can improve the situation where iron settles at the negative electrode and destroys the formation of SEI film, thereby improving the cycle performance of the battery.

[0090] The consistency index PDI of the primary particle size distribution of the positive electrode material of the present application satisfies the above range, which is beneficial to control the concentration and uniformity of the primary particle size of the positive electrode material, reduce the precipitation of small particle metal ions and / or reduce the side reaction of large particles with the electrolyte after crushing.

[0091] In some embodiments, the weight content of the carbon in the positive electrode material is 1.2%-2.0%, for example, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% or a range consisting of any of the above values; and / or,

[0092] The weight content of the M element in the positive electrode material is 297ppm-10 4 ppm, optional 10 3 ppm-10 4 ppm or 297ppm-2.5×10 3 ppm, and 2×10 3 ppm-6×10 3 ppm, such as 297ppm, 350ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 1000ppm, 1100ppm, 1200ppm, 1 500ppm, 1700ppm, 2000ppm, 2200ppm, 2500ppm, 3000ppm, 4000ppm, 5000ppm, 7000ppm, 9000ppm, 10 4 ppm or any range consisting of the above values.

[0093] This is conducive to obtaining a coating layer with thin thickness, good integrity, high density, high uniformity, and high degree of graphitization, thereby improving the cycle performance of the battery.

[0094] In some embodiments, the Dv50 particle size of the positive electrode material is 0.6-1.5 μm, for example, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm or a range consisting of any of the above values; and / or,

[0095] The compaction density of the positive electrode material at 221.55 MPa is ≥ 2.3 g / cm 3 , optional 2.3-2.6g / cm 3 , for example 2.3 g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 Or any range consisting of the above values.

[0096] This is conducive to obtaining a positive electrode sheet with high compactness and high compaction density.

[0097] In the present application, the powder resistivity can be measured by conventional methods in the art, for example, with reference to the national standard GB / T33822-2017. Specifically, a powder resistivity meter is used to test the sample, a pressure of 8 MPa is applied, and the forward resistivity and reverse resistivity of the sample are tested respectively, and the average value of the two is taken as the powder resistivity of the sample.

[0098] In the present application, the BET specific surface area can be determined by conventional methods in the art, for example, with reference to the national standard GB / T19587-2017. Specifically, it can be tested using a specific surface area analyzer, with the sample loaded in a special sample tube, heated and vacuumed for degassing; the sample tube containing the sample is placed in a workstation, the adsorption gas is nitrogen, the test atmosphere is high-purity liquid nitrogen, and the adsorption amount of the gas on the solid surface under different relative adsorption pressures is measured. The analyzer automatically calculates the BET specific surface area based on the BET multilayer adsorption theory and formula.

[0099] In the present application, the consistency index PDI value of the primary particle size distribution can be determined by conventional methods in the art; for example, an argon ion beam is used to cut the surface of the positive electrode perpendicularly, and the cross section is photographed by a scanning electron microscope, and the particle size of the primary particles with a particle size greater than 50nm is counted, and the PDI is calculated according to the following formula; wherein, the average particle size It is the sum of the particle sizes of the primary particles divided by the number of primary particles;

[0100]

[0101]

[0102] Where σ is the standard deviation of particle size, is the average particle size, x i is the particle size of the primary particles, and n is the total number of primary particles counted.

[0103] In the present application, the amount of iron dissolved per gram of the positive electrode material in 100 mL of hydrochloric acid solution (0.01 mol / L) can be determined by conventional methods in the art, for example, a dilute hydrochloric acid solution (0.01 mol / L) is added to the positive electrode material, sealed and stirred, sealed and allowed to stand at room temperature, the supernatant is filtered, and the concentration of Fe element in the filtrate is tested by ICP-OES, and the amount of iron dissolved per gram of the positive electrode material in 100 mL of hydrochloric acid solution is calculated.

[0104] In the present application, the Dv50 particle size can be measured by conventional methods in the art, such as adding deionized water to the material to completely disperse the sample, and the sample concentration ensures that the light shielding degree is 8-12%. The Dv50 particle size of the material is measured by a laser particle size analyzer.

[0105] In the present application, the compaction density can be measured by conventional methods in the art, for example, the sample powder is placed in a compaction density mold, placed in a compaction density machine, and then compacted with a certain pressure and then tested for compaction density.

[0106] [Method for preparing positive electrode material]

[0107] One embodiment of the present application provides a method for preparing a positive electrode material, comprising:

[0108] Ball-milling and sand-milling an iron source, a lithium source, a phosphorus source, an organic carbon source and an inorganic carbon source in a solvent to obtain a mixture;

[0109] Drying and sintering the mixture to obtain a positive electrode material;

[0110] The positive electrode material is the positive electrode material mentioned above.

[0111] Therefore, the present application adopts the above-mentioned raw materials and combines them with operations such as ball milling, sand milling, and sintering, and optionally adds doping elements in the coating layer, so that the powder resistivity and BET specific surface area of ​​the positive electrode material meet the above-mentioned ranges, so that the prepared positive electrode material has both a lower water absorption rate and a lower water absorption contact area, thereby reducing the water absorption of the positive electrode material and reducing the occurrence of side reactions between water in the positive electrode material and the electrolyte, thereby improving the cycle performance of the battery.

[0112] In some embodiments, the organic carbon source includes a small molecule organic carbon source and a medium molecule organic carbon source, or includes a small molecule organic carbon source and a high molecule organic carbon source.

[0113] In some embodiments, the weight ratio of the small molecule organic carbon source to the medium molecule organic carbon source or the weight ratio of the small molecule organic carbon source to the high molecule organic carbon source is 1:9-9:1, and can be more preferably 1:8-2:1, for example, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or any range thereof; and / or,

[0114] The molar mass of the small molecule organic carbon source is less than or equal to 500 g / mol; and / or,

[0115] The weight average molecular weight of the medium molecular organic carbon source is greater than 500 and less than or equal to 2000; and / or,

[0116] The weight average molecular weight of the polymer organic carbon source is greater than 2000 and less than or equal to 1000000; and / or,

[0117] The inorganic carbon source includes one or more of acetylene black, Ketjen black, graphite oxide, graphene, and carbon nanotubes.

[0118] This is conducive to forming a coating layer with good density and integrity, thereby reducing the iron dissolution amount and powder resistivity of the positive electrode material.

[0119] In some embodiments, the organic carbon source includes one or more of glucose, sucrose, fructose, citric acid, starch, polyvinyl alcohol, polyethylene glycol, and polyaniline.

[0120] In some embodiments, in the step of preparing the mixture, the iron source, lithium source, phosphorus source, organic carbon source, inorganic carbon source, and source of element M are ball-milled or sand-milled in a solvent to obtain a mixture.

[0121] In some embodiments, the core comprises Li 1+e M f Fe a PO4, wherein 0≤e<0.1 (e.g., 0, 0.001, 0.003, 0.005, 0.007, 0.008, 0.009, 0.01, 0.02, 0.04, 0.05, 0.07, 0.08, 0.09, 0.095 or any range thereof), 0≤f≤0.05 (e.g., 0, 0.001, 0.003, 0.005, 0.007, 0.008, 0.009 , 0.01, 0.02, 0.04, 0.05 or any range consisting of the above values), 0.95≤a≤1 (for example, 0.95, 0.96, 0.97, 0.98, 0.99, 1 or any range consisting of the above values); the M element includes one or more elements of Group IIA, Group IIIA, Group IVA, Group IVB, and Group VB, and can be selected to include one or more elements of Si, Al, B, Mg, Zr, Ti, Nb, and V.

[0122] In some embodiments, the weight ratio of the inorganic carbon source to the iron element in the iron source is 1:50-1:345, optionally 1:50-1:200, and more optionally 1:50-1:172.5, for example 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:119, 1:120, 1:130, 1:132.7, 1:140, 1:150, 1:172.5, 1:290, 1:300, 1:310, 1:320, 1:330, 1:340, 1:345 or a range consisting of any of the above values.

[0123] In some embodiments, the Dv50 particle size of the insoluble particles in the mixture is 0.40-0.85 μm, such as 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.85 μm or any range thereof; and / or,

[0124] The sanding temperature is 25°C-35°C, for example, 25°C, 27°C, 30°C, 32°C, 35°C or any range thereof; and / or,

[0125] The sanding time is 0.5-4 hours, for example 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4 hours or any range thereof; and / or,

[0126] The sanding is performed at a rotation speed of 5000-10000 rpm, for example, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 10000 rpm or a rotation speed within a range composed of any of the above numerical values.

[0127] This is beneficial to improving the consistency of the primary particle size distribution of the positive electrode material, improving the concentration and uniformity of the positive electrode material particles, reducing the precipitation of small particle metal ions and / or the side reaction of large particles with the electrolyte after crushing, and improving the cycle performance of the battery.

[0128] In some embodiments, before sintering, the dried mixture is granulated to obtain particles; wherein the average particle size of the particles is 2 mm-10 mm, for example, 2 mm, 4 mm, 6 mm, 8 mm, 1 cm or a range consisting of any of the above values; and / or,

[0129] After sintering, the sintered product is crushed to obtain the positive electrode material.

[0130] This is beneficial to improving the consistency of the primary particle size distribution of the positive electrode material.

[0131] In some embodiments, after drying or granulation, the temperature is uniformly increased to the sintering temperature within 2.5-9 hours, and can be uniformly increased to the sintering temperature within 3-9 hours, for example, within 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9 hours or any range of the above values; and / or,

[0132] The sintering temperature is 600°C-800°C, for example, 600°C, 620°C, 650°C, 670°C, 700°C, 720°C, 750°C, 770°C, 790°C, 800°C or any range thereof; and / or,

[0133] The sintering time is 5-10 hours, for example, 5, 6, 7, 8, 9, 10 hours or any range thereof; and / or,

[0134] Heating and sintering in a reducing atmosphere; and / or,

[0135] The volume content of the reducing gas in the reducing atmosphere is 2%-8%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8% or any range thereof.

[0136] Therefore, on the one hand, it is beneficial to fully crack and carbonize the organic carbon source to obtain an ultra-thin coating layer with a high degree of graphitization; on the other hand, it is beneficial to improve the uniformity of the coating layer and reduce the problem of metal ion dissolution caused by uneven or incomplete coating.

[0137] In some embodiments, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is 0.96-0.98, such as 0.95, 0.97, 0.98 or any range thereof; and / or,

[0138] The molar ratio of the lithium element in the lithium source to the iron element in the iron source is 1.015-1.045, for example, 1.015, 1.018, 1.02, 1.025, 1.03, 1.035, 1.04, 1.045 or any range thereof; and / or,

[0139] The molar ratio of the M element to the iron element in the iron source is 1:1000-3:100, and can be 2:1000-3:100, for example, 1:1000, 1:900, 1:800, 1:700, 1:600, 1:500, 1:400, 1:300, 1:200, 1:100, 2:100, 3:100 or any range thereof; and / or,

[0140] The Dv50 particle size of the insoluble particles in the ball-milled material is 2.0-5.0 μm, for example, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm or a range consisting of any of the above numerical values.

[0141] In some embodiments, the iron source includes one or more of an oxide, a hydroxide, a simple substance, and a salt of the iron element, and may be selected from one or more of ferric phosphate, ferric oxide, ferrous oxalate, iron powder, and ferric nitrate; and / or,

[0142] The lithium source includes one or more of lithium oxides, hydroxides, simple substances, and salts, and may be selected from one or more of lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium nitrate, lithium carbonate, lithium phosphate, lithium hydroxide, and lithium acetate; and / or,

[0143] The phosphorus source includes one or more of an acid or a salt of phosphorus, and may be selected from one or more of diammonium phosphate, ammonium phosphate, lithium phosphate, phosphoric acid, and iron phosphate; and / or,

[0144] The source of the M element includes one or more of an oxide, a hydroxide, a simple substance, and a salt of the M element; and / or,

[0145] The solvent is water.

[0146] In some embodiments, the ratio of the total mass of the iron source, lithium source, and phosphorus source to the mass of the solvent is (1-3):(1-7), for example, 1:1, 1:2, 1:3, 1:4, 1:6, 1:7, 1.5:1, 2:1, 3:1 or a range consisting of any of the above values.

[0147] In some embodiments, the ball milling temperature is 25-35°C, such as 25°C, 30°C, 35°C or any range thereof; and / or,

[0148] The ball milling time is 0.5-4 h, for example 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4 h or any range thereof; and / or,

[0149] The milling is performed at a rotation speed of 800-2000 rpm, for example, at a rotation speed of 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1400 rpm, 1500 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm or any range thereof.

[0150] In some embodiments, the drying is spray drying; optionally, the inlet air temperature of the spray drying is 200°C-300°C, and the outlet air temperature is 90°C-120°C.

[0151] In some embodiments, the reducing gas is carbon monoxide and / or hydrogen.

[0152] In some embodiments, the reducing atmosphere further includes an inert gas; optionally, the inert gas is nitrogen and / or argon.

[0153] In some embodiments, the fragmentation is by gas fragmentation.

[0154] [Positive electrode]

[0155] The positive electrode plate generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the aforementioned positive electrode material.

[0156] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0157] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0158] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0159] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0160] In some embodiments, the positive electrode material may further include positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc.

[0161] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0162] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0163] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0164] [Negative electrode]

[0165] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.

[0166] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0167] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0168] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0169] In some embodiments, the negative electrode film layer may further include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0170] In some embodiments, the negative electrode film layer may further include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0171] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0172] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0173] [Electrolytes]

[0174] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0175] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0176] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0177] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0178] In some embodiments, the electrolyte may further include additives. As examples, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0179] [Isolation film]

[0180] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0181] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0182] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0183] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0184] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0185] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0186] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0187] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0188] Figure 3 4 is an example of a battery module. Figure 3In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0189] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0190] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0191] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0192] In addition, the present application also provides an electrical device, which includes at least one of the battery cells, battery modules, or battery packs provided in the present application. The battery cells, battery modules, or battery packs can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0193] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0194] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of battery cells, a battery pack or a battery module can be used.

[0195] [Example]

[0196] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0197] Example 1

[0198] (1) Preparation of positive electrode materials:

[0199] 15.081 kg of FePO4, 3.694 kg of Li2CO3, 0.425 kg of glucose, 0.200 kg of PEG 6000, 0.127 kg of Ketjen black, 0.280 kg of tetrabutyl titanate and 10 L of water were added to a 50 L stainless steel stirred mill, and ball-milled at 25 °C and 1000 rpm for 1 h to obtain a ball-milled mixed solution, wherein the Dv50 particle size of the insoluble particles in the ball-milled mixed solution was 4 ± 0.20 μm;

[0200] The ball-milled mixed solution was transferred into a sand mill, and sand-milled at 8000 rpm for 1 h at 25° C. to obtain a sand-milled mixed solution, wherein the Dv50 particle size of the insoluble particles in the sand-milled mixed solution was 0.50±0.20 μm;

[0201] The mixed liquid after sand milling is spray dried; during the spray drying process, the air inlet temperature is 300°C and the air outlet temperature is 200°C to obtain dry powder;

[0202] The dried powder was placed in a tubular furnace and heated to 780°C at a uniform rate for 6 hours in a nitrogen atmosphere. The powder was then sintered at 780°C for 6 hours. The sintered material was crushed by gas crushing, and the Dv50 particle size of the crushed material was controlled to be 1 μm to obtain the positive electrode material.

[0203] (2) Preparation of positive electrode sheets: The positive electrode material, binder polyvinylidene fluoride (PVDF), and conductive agent carbon black are dissolved in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, and the mixture is stirred thoroughly to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut to obtain positive electrode sheets.

[0204] (3) Negative electrode: metallic lithium sheet.

[0205] (4) Isolation membrane: Celgard 2400 microporous polyethylene membrane.

[0206] (5) Preparation of electrolyte: Ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1, and then LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte. The concentration of LiPF6 in the electrolyte was 1 mol / L.

[0207] (6) Preparation of button cells:

[0208] In an argon-protected glove box, the positive electrode sheet, negative electrode sheet, isolation membrane and electrolyte are assembled into a button cell.

[0209] The secondary battery preparation methods of Examples 2-18 and Comparative Examples 1-4 are similar to those of Example 1, and the different preparation parameters are detailed in Table 1. The weight ratio of the organic carbon source to the inorganic carbon source is the same as that in Example 1.

[0210]

[0211]

[0212] Material testing and battery testing

[0213] (1) Test of core chemical formula and carbon content:

[0214] Weigh the positive electrode material into a 100mL beaker, add 10mL of 10% w / w nitric acid solution, heat and digest at 120°C for 0.5 hour, and make up to volume with a 100mL volumetric flask; use a pipette to transfer 1mL to a 100mL volumetric flask and make up to volume to obtain the solution to be tested.

[0215] An inductively coupled plasma optical emission spectrometer (ICP-OES, instrument brand: Agilent 5800) was used to determine the contents of lithium, iron, phosphorus, oxygen, and doping elements in the test solution, calculate the element ratio in the material, and determine the chemical formula.

[0216] Weigh 0.1g of positive electrode material, add 1.5g of flux metal tungsten particles to mix, put it into a high-frequency infrared carbon-sulfur analyzer for sintering and test the weight percentage of carbon in the positive electrode material.

[0217] (2) Test of powder resistivity:

[0218] Refer to the national standard GB / T 33822-2017. Use a powder resistivity meter (Suzhou Jingge, ST2722 model), weigh 1g of sample (error within ±0.005g), add it to the feeding chamber, apply 8MPa pressure, test the forward resistivity and reverse resistivity of the sample respectively, and take the average of the two as the powder resistivity of the sample.

[0219] (3) BET specific surface area test:

[0220] Refer to GB / T 19587-2017. The specific surface area analyzer (TRISTAR 302) was used for the test. An appropriate amount of sample was placed in a special sample tube, heated and vacuumed for 2 hours, and the total weight was weighed after cooling to room temperature. The sample mass was obtained by subtracting the mass of the sample tube. The sample tube containing the sample was placed in a workstation. The adsorption gas was nitrogen. The adsorption relative pressure points were: 0.05 / 0.10 / 0.15 / 0.20 / 0.25 / 0.30, the equilibrium time was 5 seconds, and the test atmosphere was high-purity liquid nitrogen. The adsorption amount of gas on the solid surface under different relative adsorption pressures was measured. The analyzer automatically calculated the BET specific surface area based on the BET multilayer adsorption theory and formula.

[0221] (4) Test of iron dissolution:

[0222] Weigh 5.00g of positive electrode material powder in a 250mL beaker, accurate to 0.01g, add 100mL of 0.01mol / L hydrochloric acid solution with a measuring cylinder, add a stirring magnet, seal the beaker with a sealing film, and stir at 1200r / min for 30min; place the beaker in a 25℃ constant temperature water bath, seal it and let it stand for 2h, quickly draw about 10mL of the upper clear liquid with a disposable syringe, and quickly filter it with a 0.22μm needle microporous filter; use ICP-OES to test the concentration of Fe element in the filtrate, calculate the total weight of iron element in the beaker solution, and then divide it by the weight of the positive electrode material to obtain the amount of iron dissolved per gram of positive electrode material in 100mL of hydrochloric acid solution.

[0223] (5) Test of the consistency index PDI value of primary particle size distribution:

[0224] The surface of the positive electrode was cut vertically with an argon ion beam, and the cross section was photographed with a scanning electron microscope. The particle size of primary particles larger than 50 nm was counted, and the PDI was calculated according to the following formula; where the average particle size It is the sum of the particle sizes of the primary particles divided by the number of primary particles;

[0225]

[0226]

[0227] Where σ is the standard deviation of particle size, is the average particle size, x i is the particle size of the primary particles, and n is the total number of primary particles counted.

[0228] (6) Test of Dv50 particle size of positive electrode materials, Dv50 particle size of insoluble particles in mixtures or materials after ball milling:

[0229] 0.1g of positive electrode material, mixture or ball-milled material, add 1% special dispersant and 20mL deionized water, and ultrasonically treat for 5 minutes (53KHz, 120W) to completely disperse the sample. The sample concentration ensures that the shading degree is 8-12%. The Dv50 particle size of the particles is measured using a laser particle size analyzer (MasterSizer 3000); test parameters: refractive index 1.692, absorbance 1.0, test time 6s, test snap number 6000 times, test cycle number 3 times.

[0230] (7) The average particle size of the granulated particles is determined by the length-diameter statistical method;

[0231] (8) Compaction density test:

[0232] Weigh 1 g of sample powder and place it in a compaction density mold, put it into a compaction density machine, and test the compaction density after compaction at a pressure of 221.55 MPa.

[0233] (9) SEM test: The positive electrode material was tested using SEM.

[0234] The SEM photo of the positive electrode material of Example 1 is as follows Figure 7 shown.

[0235] (10) Cycle performance test method:

[0236] Place the battery in a 25℃ oven and let it stand for 2h, keeping the battery temperature at 25℃; charge to 3.65V at 1C constant current, continue constant voltage charging until the charging current is less than 0.05C; let it stand for 5min, discharge to 2.5V at 1C constant current, test the discharge capacity, this is one charge and discharge cycle; pause for 5min, repeat the above operations continuously, and measure the number of cycles when the battery capacity decays to 80% of the first discharge capacity.

[0237] The above results are shown in Table 2.

[0238] Table 2: Performance test results of Examples 1-18 and Comparative Examples 1-4

[0239]

[0240] According to the above results, we can know that:

[0241] Compared with the powder resistivity of comparative examples 1 and 4 being greater than 20Ω·cm, the battery of examples 1-18 of the present application has better cycle performance;

[0242] Compared with the powder of Comparative Example 2, the resistivity of the powder is greater than 20Ω·cm and the BET specific surface area is greater than 14m 2 / g, the cycle performance of the battery in Examples 1-18 of the present application is better;

[0243] Compared with the BET specific surface area of ​​comparative example 3, it is less than 6m 2 / g, the cycle performance of the battery in Examples 1-18 of the present application is better;

[0244] Compared with the lower content of M element in the positive electrode material of Example 15, the cycle performance of the batteries of Examples 1, 4, and 14 of the present application is better;

[0245] Compared with Example 16 in which the weight ratio of the inorganic carbon source to the iron element in the iron source is relatively small when preparing the positive electrode material, the battery of Examples 1, 4, 6, 13, and 14 of the present application has better cycle performance;

[0246] Compared with the lower content of M element in the positive electrode material of Example 17, the cycle performance of the battery in Example 2 of the present application is better;

[0247] Compared with Example 18 which is not granulated and has a larger consistency index PDI value of the primary particle size distribution of the positive electrode material, the battery of Examples 1, 4, 7-8 of the present application has better cycle performance.

[0248] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode material, comprising a core and a coating layer covering the core, The core includes lithium iron phosphate or lithium iron phosphate containing M element, The coating layer includes carbon or carbon and M element; in, The M elements in the core and the coating layer independently include one or more elements of Group IIA, Group IIIA, Group IVA, Group IVB, and Group VB; Furthermore, the positive electrode material satisfies: Powder resistivity at 8 MPa ≤ 20 Ω·cm; and, The BET specific surface area at liquid nitrogen temperature is 6-15.2 m 2 / g.

2. The positive electrode material according to claim 1, wherein The powder resistivity of the positive electrode material at 8 MPa is ≤10Ω·cm; and / or, The BET specific surface area of ​​the positive electrode material at liquid nitrogen temperature is 8-11 m 2 / g; and / or, The M elements in the core and the coating layer independently include one or more elements of Si, Al, B, Mg, Zr, Ti, Nb, and V.

3. The positive electrode material according to claim 1 or 2, wherein The amount of iron dissolved per gram of the positive electrode material in 100 mL of hydrochloric acid solution is ≤ 60 ppm; and / or, The primary particle size distribution consistency index (PDI) of the positive electrode material is ≤0.

87.

4. The positive electrode material according to any one of claims 1 to 3, wherein The amount of iron dissolved per gram of the positive electrode material in 100 mL of hydrochloric acid solution is ≤55 ppm; and / or, The primary particle size distribution consistency index (PDI) of the positive electrode material is ≤0.

4.

5. The positive electrode material according to any one of claims 1 to 4, wherein The weight content of carbon in the positive electrode material is 1.2%-2.0%; and / or, The weight content of the M element in the positive electrode material is 297ppm-10 4 ppm.

6. The positive electrode material according to any one of claims 1 to 5, wherein The weight content of the M element in the positive electrode material is 10 3 ppm-10 4 ppm.

7. The positive electrode material according to any one of claims 1 to 6, wherein The Dv50 particle size of the positive electrode material is 0.6-1.5 μm; and / or, The compaction density of the positive electrode material at 221.55 MPa is ≥ 2.3 g / cm 3 .

8. A method for preparing a positive electrode material, comprising: Ball-milling and sand-milling an iron source, a lithium source, a phosphorus source, an organic carbon source and an inorganic carbon source in a solvent to obtain a mixture; Drying and sintering the mixture to obtain a positive electrode material; The positive electrode material is the positive electrode material according to any one of claims 1 to 7.

9. The method according to claim 8, wherein: The organic carbon source includes a small molecule organic carbon source and a medium molecule organic carbon source, or includes a small molecule organic carbon source and a high molecule organic carbon source.

10. The method according to claim 9, wherein: The weight ratio of the small molecule organic carbon source to the medium molecule organic carbon source or the weight ratio of the small molecule organic carbon source to the high molecule organic carbon source is 1:9-9:1; and / or, The weight average molecular weight of the medium molecular organic carbon source is greater than 500 and less than or equal to 2000; and / or, The weight average molecular weight of the polymer organic carbon source is greater than 2000 and less than or equal to 1000000; and / or, The inorganic carbon source includes one or more of acetylene black, Ketjen black, graphite oxide, graphene, and carbon nanotubes.

11. The method according to any one of claims 8 to 10, wherein in the step of preparing the mixture, the iron source, lithium source, phosphorus source, organic carbon source, inorganic carbon source, and source of element M are ball-milled or sand-milled in a solvent to obtain the mixture.

12. The method according to any one of claims 8 to 11, wherein: The weight ratio of the inorganic carbon source to the iron element in the iron source is 1:50-1:

345.

13. The method according to any one of claims 8 to 12, wherein: The Dv50 particle size of the insoluble particles in the mixture is 0.40-0.85 μm; and / or, The sanding temperature is 25°C-35°C; and / or, The sanding time is 0.5-4 hours; and / or, Sand at 5000-10000 rpm.

14. The method according to any one of claims 8 to 13, wherein: The method further comprises: before sintering, granulating the dried mixture to obtain particles; wherein the average particle size of the particles is 2 mm-10 mm; and / or, The method further comprises: after sintering, crushing the sintered product to obtain a positive electrode material.

15. The method according to any one of claims 8 to 14, wherein: After drying or granulation, the temperature is raised to the sintering temperature at a uniform rate within 2.5-9 hours; and / or, The sintering temperature is 600° C.-800° C.; and / or, The sintering time is 5-10 hours; and / or, Heating and sintering in a reducing atmosphere; and / or, The volume content of the reducing gas in the reducing atmosphere is 2%-8%.

16. The method according to any one of claims 8 to 15, wherein: The molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is 0.96-0.98; and / or, The molar ratio of the lithium element in the lithium source to the iron element in the iron source is 1.015-1.045; and / or, The molar ratio of the M element to the iron element in the iron source is 1:1000-3:100; and / or, The Dv50 particle size of the insoluble particles in the ball-milled material is 2.0-5.0 μm.

17. A positive electrode sheet, comprising the positive electrode material according to any one of claims 1 to 7 or the positive electrode material prepared by the method according to any one of claims 8 to 16.

18. A battery comprising the positive electrode material according to any one of claims 1 to 7, the positive electrode material prepared by the method according to any one of claims 8 to 16, or the positive electrode sheet according to claim 17.

19. An electrical device comprising the battery according to claim 18.

Citation Information

Patent Citations

  • High-rate lithium iron phosphate positive electrode material, preparation method thereof, positive electrode of high-rate lithium iron phosphate positive electrode material and battery

    CN114725318A

  • Carbon-coated lithium iron phosphate positive active material, preparation method thereof, positive pole piece containing carbon-coated lithium iron phosphate positive active material and lithium ion battery

    CN116601798A

  • Positive electrode active material and preparation method therefor, positive electrode sheet, secondary battery, battery module, battery pack, and electric device

    WO2024000427A1

Cited By

  • Positive electrode active material, preparation method and detection method thereof, positive electrode plate, battery and electric equipment

    CN121617956A

  • Positive electrode material and preparation method therefor, positive electrode sheet, battery and electric device

    WO2025148536A1